Genome‐Wide Association Study of Lean Nonalcoholic Fatty Liver Disease Suggests Human Leukocyte Antigen as a Novel Candidate Locus. Issue 8 (19th May 2020) - Yoshida, Ken; Yokota, Kazuha; Kutsuwada, Yukinobu; Nakayama, Kazuhiro; Watanabe, Kazuhisa; Matsumoto, Ayumi; Miyashita, Hiroshi; Khor, Seik‐soon; Tokunaga, Katsushi; Kawai, Yosuke; Nagasaki, Masao; Iwamoto, Sadahiko
Abstract : Nonalcoholic fatty liver disease (NAFLD) is supposed to manifest its metabolic phenotype in the liver, but it is common to have lean individuals diagnosed with NAFLD, known as lean NAFLD. We conducted a two‐stage analysis to identify NAFLD‐associated loci in Japanese patients. In stage I, 275 metabolically healthy normal‐weight patients with NAFLD were compared with 1, 411 non‐NAFLD controls adjusted for age, sex, and alcohol consumption by a genome‐wide association study (GWAS). In stage II, human leukocyte antigen ( HLA ) in chromosome 6 (chr6) ( P = 6.73E‐08), microRNA (MIR) MIR548F3 in chr7 ( P = 4.25E‐07), myosin light chain 2 ( MYL2 ) in chr12 ( P = 4.39E‐07), and glycoprotein precursor ( GPC ) 6 in chr13 ( P = 5.43E‐07), as suggested by the GWAS, were assessed by single nucleotide polymorphism (SNP) association analysis of whole NAFLD against non‐NAFLD in 9, 726 members of the general population. A minor allele of the secondary lead SNP in chr6, rs2076529, was significantly associated (odds ratio [OR], 1.19; 95% confidence interval [CI], 1.11‐1.28; P = 2.10E‐06) and the lead SNP in chr7 was weakly associated (OR 1.15; 95% CI, 1.04‐1.27; P = 6.19E‐03) with increased NAFLD risk. Imputation‐based typing of HLA showed a significant difference in the distribution of HLA‐B, HLA‐ DR‐beta chain 1 ( DRB1 ), and HLA‐ DQ‐beta chain 1 ( DQB1 ) alleles in lean NAFLD GWAS. Next‐generation sequence‐based typing of HLA in 5, 649 members of the general population replicated the significant difference of HLA‐B allele distribution and the significant increase of the HLA‐B*54:01 allele in whole NAFLD. Fecal metagenomic analysis of 3, 420 members of the general population showed significant dissimilarity in beta‐diversity analysis of rs2076529 and HLA‐B*54:01 allele carriers from noncarriers. Veillonellaceae was increased but Verrucomicrobia was decreased in rs2076529 minor allele and HLA‐B*54:01 allele carriers as in NAFLD. Conclusion : HLA was identified as a novel locus associated with NAFLD susceptibility, which might be affected by the alteration of gut microbiota. Abstract :